Demam Tifoid dengan Demam Dengue pada Anak Perempuan Usia 8 Tahun : Laporan Kasus - Muhammad Rafif; Mardiati Mardiati (Lembaga Pengembangan Kinerja Dosen, 2025)
Typhoid fever is one of the main causes of death and morbidity in densely populated areas and unhygienic environments. The most common causative agent of typhoid fever in children is Salmonella typhii. Typhoid fever is enteric fever with main clinical symptoms such as abdominal pain and fever. Dengue Hemorrhagic Fever (DHF) is an infectious disease caused by dengue viruses types I-IV with clinical manifestations of fever lasting 2-7 days accompanied by bleeding symptoms and if a shock occurs, the death rate is quite high. This case report is an 8 years old girl with complaints of fever accompanied by abdominal pain, nausea and vomiting and headache. On physical examination, it was found that the patient's general condition appeared to be moderately ill, composmentis consciousness, pulse 86 times/minute, respiratory rate 22 times/minute, temperature 36.5 °c, and the patient's SpO2 was found to be 98%. From the supporting examination, it was found that the tubex value increased by +4. The Dengue results showed Dengue IgG (+) and IgM (-).